Pengaruh Likuiditas,Solvabilitas, dan Profitabiltas Return Saham Perusahaan Manufaktur Subsektor Farmasi dan Perawatan Kesehatan Yang Terdaftar di BEI Periode 2019-2024 - M.Attahariq Rifqi; Susy Hambani; Yoyok Priyo Hutomo (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Assessment seeks to investigate and also investigate the various effects financial ratios, as indicated by financial ratios consisting of the current ratio (CR), debt to equity ratio (DELR), and gross profit margin (GPM), on stock returns. The study focuses on companies in the pharmaceutical and healthcare treatment sub-sector that are registered with the IDX during the period of 2019-2024, totaling 13 companies. The sample selection utilized purposive sampling, and of those, only 5 companies were included in the sample. Data processing techniques involved classical assumption testing, multiple linear regression analysis, as well as hypothesis testing using F-tests and t-tests. IBM SPSS was utilized to facilitate the data analysis. The findings revealed that the current ratio (CR) has no significant effect on stock returns, the debt to equity ratio (DELR) has a significant effect on stock returns, and the gross profit margin (GPM) has no significant impact on stock returns for companies in the manufacturing sub-sector of pharmaceuticals and healthcare treatment registered with the IDX during the 2019-2024 period.